2013
DOI: 10.1186/1471-2466-13-57
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and costs of home-based pulmonary rehabilitation in chronic obstructive pulmonary disease - a multi-centre randomised controlled equivalence trial

Abstract: BackgroundPulmonary rehabilitation is widely advocated for people with chronic obstructive pulmonary disease (COPD) to improve exercise capacity, symptoms and quality of life, however only a minority of individuals with COPD are able to participate. Travel and transport are frequently cited as barriers to uptake of centre-based programs. Other models of pulmonary rehabilitation, including home-based programs, have been proposed in order to improve access to this important treatment. Previous studies of home-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 47 publications
(60 reference statements)
1
53
0
1
Order By: Relevance
“…30 The use of telecommunication technologies in the delivery of exercise rehabilitation programs for patients with cardiopulmonary diseases is emerging. Innovative telerehabilitation studies in patients with COPD 36 and CHD 37 may shed further light on the effects of telerehabilitation compared with traditional center-based exercise.…”
Section: Discussionmentioning
confidence: 98%
“…30 The use of telecommunication technologies in the delivery of exercise rehabilitation programs for patients with cardiopulmonary diseases is emerging. Innovative telerehabilitation studies in patients with COPD 36 and CHD 37 may shed further light on the effects of telerehabilitation compared with traditional center-based exercise.…”
Section: Discussionmentioning
confidence: 98%
“…In pharmacological trials patients are often excluded because of co-morbid conditions or current medication use [34]. Patients for non-pharmacological trials have been recruited from pulmonary specialty clinics [39,40] or after exacerbations or hospitalizations [34,35,41]. For most clinical interventions, available evidence to assess effectiveness is usually limited to efficacy with limited evidence on reach, and little or no evidence on adoption, implementation, or maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Herland et al 35 found that a 'typical' clinical study would only include 17% of the 'real-life' asthma or COPD patient population, potentially limiting the generalisation of study findings to 'real-life' settings. Changes in physical performance are a common endpoint in COPD studies evaluating pharmacological 36 and non-pharmacological 37 interventions, and this review demonstrates existing evidence for the potentially confounding influence of co-morbidity on such results.…”
Section: Authormentioning
confidence: 99%